An Effective Strategy toward High‐Efficiency Fluorescent OLEDs by Radiative Coupling of Spatially Separated Electron–Hole Pairs. Issue 10 (26th February 2018) - Li, Binbin; Gan, Lin; Cai, Xinyi; Li, Xiang‐Long; Wang, Zhiheng; Gao, Kuo; Chen, Dongcheng; Cao, Yong; Su, Shi‐Jian
Abstract: An effective strategy toward low‐driving voltage and high‐efficiency fluorescent organic light‐emitting diodes (OLEDs) by long‐range radiative coupling of spatially separated electron–hole pairs is proposed. Charge transfer excited states between p‐type hole‐transport layer and n‐type electron‐transport layer can be achieved although they are separated by an interlayer, giving significantly reduced efficiency roll‐off and higher luminance compared with the devices based on interface exciplex. Remarkable external quantum efficiency near 15% is also achieved by employing conventional red fluorescent dyes doped into the hole‐transport layer adjacent to the interlayer due to the avoidance of the direct carrier trapping and thus the generation of unwanted nonradiative triplet excitons. Different from the conventional devices with a host–guest structure for both exciton generation and energy releasing, such unique device concept provides a bright avenue toward structure‐simplified and high‐performance fluorescent OLEDs, where the long‐range coupled radiative excitons and the following energy releasing are separated in their own channels. Abstract : High‐efficiency fluorescent organic light‐emitting diodes are achieved by radiative coupling of spatially separated electron–hole pairs as both the emission center and the exciton donor for conventional fluorencent emitters.